Chinese phraseology as guanyunyu - Daulet, F.; Laryonov, S.; Zhunisova, D. (Journal of Oriental Studies, 2016)
This article reveals the features of this type of Chinese phraseology as guanyunyu (customary expressions), which are the idioms of modern Chinese language. This type of idioms is widely used in Chinese, and it is constantly evolving and has a great vitality. Research and study of this linguistic phenomenon as guanyunyu has not only scientific value but also practical importance in the teaching of the Chinese language.